Neonatal Tetanus in Vietnam: Comprehensive Intensive Care Support Improves Mortality. (9th September 2015) - Trieu, Huynh T.; Lubis, Inke N.; Qui, Phan T.; Yen, Lam M.; Wills, Bridget; Thwaites, C. Louise; Sabanathan, Saraswathy
Abstract: We report a 66% reduction in neonatal tetanus mortality after introducing a new management bundle integrating antibiotic therapy, muscle relaxation and invasive monitoring. The latter allowed rapid detection of autonomic instability which was treated with magnesium sulphate. This is the first report of its use in neonatal tetanus.